Role of foods in caries among preschool-children: A cross-sectional study: Foods and Caries - Koç, Nevra; Aslan, Nazlı Nur; Yardimci, Hülya (Progress in Nutrition, 2022)
Aim: Early childhood caries (ECC) is a chronic infectious disease that affects children and is a serious public health problem. Proper and balanced nutrition is important for preventing caries and developing immunity against infections. The aim of this study is to evaluate the relation between childhood caries and consumption of cariogenic and anti-cariogenic foods among children 30-78 months old. Materials and Methods: The study was carried out with 200 children between 30-78 months old. The questionnaire form was included sociodemographic characteristics, nutritional habits and frequency of consumption of food groups. Presence of decayed, extracted or filled teeth was recorded from dentist files and decayed-missed-filled teeth (dmft) index was calculated. Patients were divided into two groups according to dmft index as children with and without caries. The data were evaluated with proper statistical methods. Findings: During the study, 200 children (116 male, 84 female) were evaluated. Mean age was 61.4±11.9 months. Educational status of parents was related to the presence of caries (p<0.05). Presence of caries was related to regular consumption of breakfast and lunch but there was not a significant relation for dinner. Consumption of potato crisps, fizzy drinks, and sweets was more frequent among children with caries (p<0.05) whereas consumption of anti-cariogenic animal-oriented foods was more frequent among children without caries (p<0.05). Frequency of milk, yoghurt and chicken consumption was higher among caries-free children (p<0.05). Conclusions: Consumption of cariogenic foods has an important role in the occurrence of early caries among preschool children.